Vertical canopy gradient shaping the stratification of leaf-chewer-parasitoid interactions in a temperate forest - Šigut, Martin; Šigutová, Hana; Šipoš, Jan; Pyszko, Petr; Kotásková, Nela; Drozd, Pavel (Ecology and evolution, 2018)
Knowledge about herbivores and their parasitoids in forest canopies remains limited, despite their diversity and ecological importance. Thus, it is important to understand the factors that shape the herbivore-parasitoid community structure, particularly the effect of vertical gradient. We investigated a quantitative community dataset of exposed and semiconcealed leaf-chewing larvae and their parasitoids along a vertical canopy gradient in a temperate forest. We sampled target insects using an elevated work platform in a 0.2 ha broadleaf deciduous forest plot in the Czech Republic. We analyzed the effect of vertical position among three canopy levels (first [lowest], second [middle], and third [highest]) and tree species on community descriptors (density, diversity, and parasitism rate) and food web structure. We also analyzed vertical patterns in density and parasitism rate between exposed and semiconcealed hosts, and the vertical preference of the most abundant parasitoid taxa in relation to their host specificity. Tree species was an important determinant of all community descriptors and food web structure. Insect density and diversity varied with the vertical gradient, but was only significant for hosts. Both host guilds were most abundant in the second level, but only the density of exposed hosts declined in the third level. Parasitism rate decreased from the first to third level. The overall parasitism rate did not differ between guilds, but semiconcealed hosts suffered lower parasitism in the third level. Less host-specific taxa (Ichneumonidae, Braconidae) operated more frequently lower in the canopy, whereas more host-specific Tachinidae followed their host distribution. The most host-specific Chalcidoidea preferred the third level. Vertical stratification of insect density, diversity, and parasitism rate was most pronounced in the tallest tree species. Therefore, our study contradicts the general paradigm of weak arthropod stratification in temperate forest canopies. However, in the network structure, vertical variation might be superseded by variation among tree species.
Keywords: parasitism rate; host specificity; quantitative food webs; vertical stratification; herbivore–parasitoid interactions; temperate forest canopy